2019
DOI: 10.21470/1678-9741-2019-0069
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis-Patient Mismatch Negatively Affects Outcomes after Mitral Valve Replacement: Meta- Analysis of 10,239 Patients

Abstract: Objective This study sought to evaluate the impact of prosthesis-patient mismatch on the risk of perioperative and long-term mortality after mitral valve replacement. Methods Databases were researched for studies published until December 2018. Main outcomes of interest were perioperative and 10-year mortality and echocardiographic parameters. Results The research yielded 2,985 studies for inclusion. Of these, 16 articles were analyzed, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Sixteen retrospective single‐center studies, 4‐6,10‐22 two retrospective multicenter studies, 7,23 and one prospective study 24 were included in the final review and meta‐analysis. Two studies identified were meta‐analyses 25,26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen retrospective single‐center studies, 4‐6,10‐22 two retrospective multicenter studies, 7,23 and one prospective study 24 were included in the final review and meta‐analysis. Two studies identified were meta‐analyses 25,26 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies identified were meta-analyses. 25,26 In one study, 19 a two-tailed analysis was performed and EOA was obtained from referenced values or measured with the continuity equation (CE) method. In another study, 15 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 PPM is associated with higher perioperative and long-term mortality as a result of substandard hemodynamics, pulmonary hypertension, and poor regression of left ventricular hypertrophy. 1,2 Surgical aortic root enlargement (ARE) during AVR allows for the placement of a larger size aortic valve prosthesis, reducing the risks of PPM and improving patient outcomes. 3 A posterior ARE was first suggested by Nick et al in 1970.…”
Section: Introductionmentioning
confidence: 99%
“… 1 PPM is associated with higher perioperative and long-term mortality as a result of substandard hemodynamics, pulmonary hypertension, and poor regression of left ventricular hypertrophy. 1 2 …”
Section: Introductionmentioning
confidence: 99%